Effectiveness of the flipped classroom method using clinical scenarios and Educational Technology versus Subject-Based Lectures in a gastrointestinal physiology course for medical students - Seidi, Masoumeh; Ramezani-Aliakbari, Fatemeh; Doosti-Irani, Amin (BMC medical education, 2024)
Medical education is evolving towards more practical, active, effective, and student-centered approaches that address the limitations of traditional lecture methods. Recently, the flipped classroom method has been considered to support these reforms. However, research on the use of flipped classroom methods in medical education, particularly related to clinical scenarios and educational technology, is still in its early stages. This study aims to evaluate the effectiveness of the flipped classroom method using clinical scenarios and educational technology versus subject-based lectures in the course of gastrointestinal physiology for medical students. A total of 60 medical students participated in this study. The control group (n = 30) received traditional subject-based lectures and participated in question-and-answer sessions. The intervention group (n = 30) received non-attendance educational content and participated in small group discussions based on clinical scenarios. Course satisfaction was measured using an 18-item questionnaire, and learning outcomes were assessed with a 20-question multiple-choice test, corresponding to levels 1 and 2 of Kirkpatrick's model. Data were analyzed using descriptive and analytical statistical tests with SPSS software version 24. The findings indicated that the post-test scores in the intervention group were significantly higher compared to the control group. However, according to the student satisfaction questionnaire, satisfaction was significantly lower in the intervention group compared to the control group. This study demonstrated that the flipped classroom method, compared to traditional lectures, improved the learning and performance of medical students at Hamadan University of Medical Sciences in the course of gastrointestinal physiology.